Identifying the antiasthmatic target of doxofylline using immobilized β2‐adrenoceptor based high‐performance affinity chromatography and site‐directed molecular docking. Issue 10 (12th May 2016) - Zhang, Yajun; Zeng, Kaizhu; Wang, Jing; Gao, Haiyang; Nan, Yefei; Zheng, Xiaohui
Abstract : As a xanthine derivative, doxofylline is believed to be dominant for fighting against asthma in practice. Unlike other xanthines, the antiasthmatic effects of doxofylline lack any definite proof of target and mediating mechanism according to previous reports. In this work, the interaction between doxofylline and β 2 ‐AR was investigated by high performance affinity chromatography using frontal analysis and nonlinear model. The methodology involved the immobilization of β 2 ‐AR on the silica gel by a random linking method, the determination of the binding parameters by frontal analysis and nonlinear chromatography and the exploration of the binding mechanism by site‐directed molecular docking. The association constant for doxofylline binding to immobilized β 2 ‐AR was determined to be 7.70 × 10 4 M −1 by nonlinear chromatography and 5.91 × 10 4 M −1 by frontal analysis. Ser 169 and Ser 173 were the binding sites for the receptor–drug interaction on which hydrogen bond was believed to be the main driven force during the interaction. These results indicated that the antiasthmatic effects of doxofylline may be behind the mediating mechanism of β 2 ‐AR. High performance affinity chromatography based on immobilized receptor has potential to become an alternative for drug target confirmation and drug–receptor interaction analysis. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : Investigation of interaction between immobilized β 2 ‐AR and doxofylline by high‐performance affinity chromatography using frontal analysis and nonlinear model. Site‐directed molecular docking was applied to explore the binding mechanism.